Determinan Struktur Modal Perusahaan Telekomunikasi Sebelum Dan Disaat Pandemi Covid-19 - Astria Pasaribu; Annaria Magdalena Marpaung (Jurnal Informatika Kesatuan, 2023)
This study aims to prove whether Profitability, Liquidity, and Firm Size affect the Capital Structure. The research method used is multiple linear regression which is processed using SPSS 24.0. The population in this study are Telecommunication Sub-Sector companies on the Indonesia Stock Exchange in the 2016-2020 time period. Because the population of this study is relatively small, the researchers used a census data collection technique with 6 (six) telecommunication companies as objects, namely PT. Bakrie Telecom Tbk, PT. Indosat Tbk, PT. Jasnita Telecomindo Tbk, and PT. XL Axiata Tbk, PT. Smartfren Tbk, and PT. Indonesian Telecommunications. The dependent variable (Y) in this study is Capital Structure, while the independent variable (X) in this study is Profitability (X1), Liquidity (X2), and Company Size (X3). The results of this study are that profitability partially has a negative and insignificant effect on capital structure, liquidity partially has a negative and insignificant effect on capital structure, and company size partially has a positive and significant effect on capital structure, as well as profitability, liquidity, and size. companies simultaneously in certain situations affect the capital structure of the Telecommunication Sub-Sector Companies Listed on the Indonesia Stock Exchange. Researchers suggest that in future research researchers can add variables, other research objects and a longer period of time to get better results. Keywords: Profitability, Likuidity, Size, and Capital Structure